The Effect Of Servant Leadership And Motivation On Civil Apparatus (Asn) Performance With Work Discipline As An Intervening Variable: A Study At The Health Office Of West Tanjung Jabung Regency - Agnes Marisca Dian Sari; Arthur Sitaniapessy; Joko Rizkie Widokarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of servant leadership and motivation on the performance of State Civil Apparatus (ASN) with work discipline as an intervening variable at the Tanjung Jabung Barat District Health Office. The study was conducted on employees within the Tanjung Jabung Barat District Health Office, which includes office offices, 16 community health centers, and 1 Regional Technical Implementation Unit (UPTD) Pharmacy Installation. The population in this study amounted to 821 employees, consisting of 552 civil servants and 269 PPPK employees spread across all work units of the Tanjung Jabung Barat District Health Office. The sampling technique used probability sampling with a simple random sampling method, so that each member of the population has an equal opportunity to become a research respondent. The results of the study indicate that servant leadership and work motivation have a positive and significant effect on work discipline and the performance of State Civil Apparatus (ASN) at the Tanjung Jabung Barat District Health Office, while work discipline is also proven to have a positive and significant effect on ASN performance. However, work discipline is not able to significantly mediate the relationship between servant leadership and work motivation on ASN performance, so it can be concluded that the improvement in ASN performance is more directly influenced by the implementation of servant leadership and high work motivation than through work discipline as an intervening variable.